Beliefs regarding geriatrics primary care topics among medical students and internal medicine residents. Issue 1 (2nd January 2021) - Jester, Dylan J.; Hyer, Kathryn; Guerra, Lucy; Robinson, Bruce E.; Andel, Ross
ABSTRACT: This study evaluated beliefs regarding 25 content areas essential to the primary care of older adults and attitudes toward aging held by first-yearmedical students and Internal Medicine residents. A survey of 136 medical students and 61 Internal Medicine residents was conducted at an academic health-center. Beliefs were assessed by the 25-item Geriatrics Clinician-Educator Survey. Gap scores reflecting the difference in ratings between self-rated importance and knowledge were calculated. Attitudes toward aging was assessed by the Images of Aging Scale. Students and residents expressed similar beliefs about the importance of content areas, but students provided lower ratings in knowledge. Students reported larger gap scores in areas that reflected general primary care (e.g., chronic conditions, medications), whereas residents reported larger gap scores in areas that reflected specialists' expertise (e.g., driving risk, cognition, psychiatric symptoms). Attitudes toward aging did not differ appreciably between students and residents. Our findings suggest that primary care topics applicable for any age demographic were rated as most important by first-year medical students and Internal Medicine residents. Topics relevant to older populations–-particularly those requiring specialists' knowledge of or requiring sensitive discussion with older adults—were rated as less important and were less well-mastered.